Analisis Safety Factor Corrugated Concrete Sheet Pile (CCSP) Pada Pekerjaan Pengaman Tanggul Sungai Bogowonto Hilir Dengan Software Plaxis - Rakhmad Cahyana; Edy Purwanto (JURNAL ILMIAH NUSANTARA, 2025)
Embankment design planning in flood control infrastructure development plays a crucial role in determining the construction form and function. Therefore, several structural design options are necessary. One type of embankment structure is an embankment with parapet walls and Corrugated Concrete Sheet Pile (CCSP) reinforcement. Therefore, based on this problem, a scientific approach is needed to determine the appropriate embankment safety factor. One such scientific method is stability analysis using the Plaxis method. The results of this study for the stability (safety factor) using the Corrugated Concrete Sheet Pile (CCSP) method are 2,47.